Anti-inflammatory, antiallergic and COVID-19 protease inhibitory activities of phytochemicals from the Jordanian hawksbeard: identification, structure–activity relationships, molecular modeling and impact on its folk medicinal uses. Issue 62 (15th October 2020) - Ebada, Sherif S.; Al-Jawabri, Nariman A.; Youssef, Fadia S.; El-Kashef, Dina H.; Knedel, Tim-Oliver; Albohy, Amgad; Korinek, Michal; Hwang, Tsong-Long; Chen, Bing-Hung; Lin, Guan-Hua; Lin, Chia-Yi; Aldalaien, Sa'ed M.; et al.
Abstract : On Wednesday 11th March, 2020, the world health organization (WHO) announced novel coronavirus (COVID-19, also called SARS-CoV-2) as a pandemic. Abstract : On Wednesday 11 th March, 2020, the world health organization (WHO) announced novel coronavirus (COVID-19, also called SARS-CoV-2) as a pandemic. Due to time shortage and lack of either a vaccine and/or an effective treatment, many trials focused on testing natural products to find out potential lead candidates. In this field, an edible and folk medicinal Jordanian plant Crepis sancta (Asteraceae) was selected for this study. Phytochemical investigation of its enriched polyphenolic extract afforded four eudesmane sesquiterpenes (1–4 ) together with (6 S, 9 R )-roseoside (5 ) and five different methylated flavonols (6–10 ). Structure elucidation of isolated compounds was unambiguously determined based on HRESIMS, X-ray crystallography, and exhaustive 1D and 2D NMR experiments. All isolated compounds were assessed for their in vitro anti-inflammatory, antiallergic and in silico COVID-19 main protease (M pro ) inhibitory activities. Among the tested compounds, compounds 5–10 revealed potent anti-inflammatory, antiallergic and COVID-19 protease inhibitory activities. Chrysosplenetin (10 ) is considered as a promising anti-inflammatory and antiallergic lead structure adding to the phytotherapeutic pipeline. Moreover, its inhibitory activity against SARS-CoV-2 M pro, supported by docking and molecular dynamic studies, strengthens its potential as a lead structure paving the way toward finding out a natural remedy to treat and/or to control the current COVID-19 pandemic.